PELAKSANAAN DUKUNGAN SOSIAL OLEH BIDAN SELAMA KALA I PERSALINAN NORMAL DI RSUD dr. Hi. CHASAN BOESOIRIE TERNATE - Anita Vebriyanti (Jurnal Kesehatan, 2014)
Abstract : Maternal and neonatal health services is one of the elements determining the current health status. According to Word Health Organization contained 99% of maternal deaths due to labor problems or birth referred by health workers, occur in developing countries. Maternal Mortality Rate system showed a significant decrease from 1994 to 2007. The first stage of labor began his adequate and complete the cervix starts to open up (10 cm). Based on the results of a preliminary survey in the room obstetrics dr. Hi. Chasan Boesoirie Ternate carried through interviews and observations of HR midwives are 39 people. 50% of midwives have training APN. This is a descriptive analytic study is to describe the implementation of social support by midwives during the first stage of normal labor in dr. Hi. Chasan Boesoirie Ternate 2013. Descriptive method is a method in researching the status of a group of people, an object, a condition, a system of thought, or even a class of events in the present. The purpose of descriptive research is to create a description, picture or painting in a systematic, factual and accurate information on the facts, the properties and the relationship between the phenomena investigated. The research was carried out in Obstetrics and Gynecology Obstetrics Space dr. Hi. Chasan Boesoirie Tenate, and a sufficient sample research within easy reach of researchers. The population in this study was a midwife who worked in the area of obstetrics dr. Hi. Chasan Boesoirie Ternate include obstetrics and dinekologi space. The number of midwives during the study as many as 38 people. The sample in this study was a midwife who helped deliver in Space Midwifery dr. Hi. Chasan Boesoirie Ternate